Evaluation of climate justice in open green spaces based on landscape metrics: the case of Istanbul - Sokmen, Eren Dagra; Aksoy, Onur (Springer, 2025)
Rapid urbanisation leads to a rapidly growing population in cities, causing an unequal distribution and resulting in climate injustices. In areas with insufficient green infrastructure, this creates unhealthy conditions and a strong Urban Heat Island (UHI) effect. This study was conducted in 18 districts of Istanbul. The aim of this study is to evaluate the impact of green spaces on the UHI effect using landscape metrics, and to propose green space strategies for areas affected by climate injustice. In this context, NDVI analysis was performed to identify green spaces using images from the Sentinel-2 A satellite. Additionally, Land Surface Temperature (LST) was calculated from Landsat 8 OLI/TIRS satellite images, and the landscape metrics of green spaces in UHI and non-UHI areas were analysed using Fragstats software. In the final stage, statistical analyses including t-tests, Mann-Whitney U tests, and Pearson and Spearman correlation analyses were conducted to examine the relationship between LST and the landscape metrics. The study shows that Zeytinburnu and Ka & gbreve;& imath;thane are climatically unjust, despite having average green space. The reason for these districts to have more UHI areas than others is their limited green spaces, which is characterized by a smaller size than other districts. In addition, the results of statistical tests revealed that differences in LST and landscape metrics between UHI and non-UHI areas were statistically significant, except for the connectivity metric. Correlation analyses showed that LST had a strong negative correlation with CA, PLAND, LPI, TE, ED, and MPS; a moderate negative correlation with NP and PD; and a weak positive correlation with connectivity. All these findings highlight that future open green space designs must consider metrics such as class area, percentage of landscape, number of patches, mean patch size, patch density, largest patch index, total edge, and edge density. Based on these findings, green space proposals were developed for climatically unjust areas considering landscape metrics. The outcomes of this study are unique because they assess climate justice through landscape metrics, providing a foundation for urban planning and design efforts in developed, developing, and less-developed countries.
Keywords: Urban heat & imath;sland; Climate justice; Open green space; Land surface temperature; Landscape metrics